1975
DOI: 10.1017/s0022029900015259
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the milk composition of West African dwarf, Red Sokoto and Saanen goats at different stages of lactation: I. Total solids, butterfat, solids-not-fat, protein, lactose and energy contents of milk

Abstract: SummaryNine West African dwarf (Fouta djallon), Red Sokoto (Maradi) and Saanen lactating goats, hand-milked, were used for these studies, which lasted 12 weeks. The Saanen goats' milk was obtained weekly from the Western State Ministry of Agriculture and Natural Resources Urban Dairy Farm at Iwo Road, while similar samples were collected from the herd at the University of Ibadan Teaching and Research Farm. The goats were balanced for stage of lactation, namely early, mid- and late-lactation. They were each mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
15
4
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 8 publications
8
15
4
1
Order By: Relevance
“…This implies that as the percentage of protein increases in bovine milk, there is a corresponding decrease in TS and SNF, but this relationship was not statistically significant (Table 2). Our finding supports an earlier observation by Mba et al . (1975) in which the correlation between protein and SNF was not statistically significant.…”
Section: Resultssupporting
confidence: 94%
“…This implies that as the percentage of protein increases in bovine milk, there is a corresponding decrease in TS and SNF, but this relationship was not statistically significant (Table 2). Our finding supports an earlier observation by Mba et al . (1975) in which the correlation between protein and SNF was not statistically significant.…”
Section: Resultssupporting
confidence: 94%
“…As the kids advanced in age from birth to 90 days, the effect of dam supplementation was reflected in their liveweight gains in agreement with the report of Ahmed et al [13]. The highest ADG value of 53.88 g·day -1 in this study fell within the range of 64 g·day -1 reported in West African Dwarf does [14][15][16], but much lower than 150 g·day -1 in Yankasa lambs [17]. The lower values in this study are justifiable given the fact that it was conducted in the long-dry season of the year when naturally grazed pasture and feed resources are critically low.…”
Section: Birth Weight and Weight Gains Of Kidssupporting
confidence: 90%
“…The lactose content was comparable to the reported values of 4.75% and 4.9% for Swedish Landrace and Boer respectively (Hosberg, 2011;Mestawet et al, 2012). The total solids mean value of 18.84% was higher than that of the West African Dwarf (18.30%) and Red Sokoto (15.85%) goat milk (Mba et al, 1975). The present total solids value was much higher than the values of 16.60% reported for Saanen (Pilla et al, 1980) and Alpine goat milk (Varna and Chawia, 1984).…”
Section: Milk Compositionsupporting
confidence: 82%
“…The present total solids value was much higher than the values of 16.60% reported for Saanen (Pilla et al, 1980) and Alpine goat milk (Varna and Chawia, 1984). Overall mean of solid-notfat was also higher than the reported values of 4.60% for Red Sokoto and 4.17% for the West African Dwarf goat milk (Mba et al, 1975). This implies that Kalahari Red goat milk will yield more products per litre of milk during cheese and butter production.…”
Section: Milk Compositionmentioning
confidence: 57%